2016
DOI: 10.1093/mnras/stw1661
|View full text |Cite
|
Sign up to set email alerts
|

Dark matter inside early-type galaxies as function of mass and redshift

Abstract: We study the behaviour of the dynamical and stellar mass inside the effective radius (r e ) of early-type galaxies (ETGs). We use several samples of ETGs -ranging from 19 000 to 98 000 objects-from the ninth data release of the Sloan Digital Sky Survey. We consider Newtonian dynamics, different light profiles and different Initial Mass Functions (IMF) to calculate the dynamical and stellar mass. We assume that any difference between these two masses is due to dark matter and/or a non Universal IMF. The main re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 63 publications
(77 reference statements)
2
16
1
Order By: Relevance
“…Indeed we can see a mild shift of the maximum at large redshift, as the maximum is close to 0.4 for nearby galaxies and close to 0.5 for distant galaxies. This result seems to be the opposite to that found in Nigoche-Netro et al (2016) and by other authors, where they found that the difference between virial and stellar mass decreases as a function of redshift. The most plausible explanation of this apparent contradiction is that the dependence of log(M Virial /MSun) -log(MStar/MSun) on mass, reported by different authors, has not been taken into account in the previous analysis.…”
Section: Frequency Distribution Of the Difference Between Dynamical Acontrasting
confidence: 99%
See 3 more Smart Citations
“…Indeed we can see a mild shift of the maximum at large redshift, as the maximum is close to 0.4 for nearby galaxies and close to 0.5 for distant galaxies. This result seems to be the opposite to that found in Nigoche-Netro et al (2016) and by other authors, where they found that the difference between virial and stellar mass decreases as a function of redshift. The most plausible explanation of this apparent contradiction is that the dependence of log(M Virial /MSun) -log(MStar/MSun) on mass, reported by different authors, has not been taken into account in the previous analysis.…”
Section: Frequency Distribution Of the Difference Between Dynamical Acontrasting
confidence: 99%
“…The density of galaxies was calculated using the third, fifth, eighth, and tenth nearest neighbours, for both the spectroscopic and photometric samples. Cappellari et al 2013;Nigoche-Netro et al 2016) and redshift (Nigoche-Netro et al 2016). In the following we will analyse the above-mentioned dependencies.…”
Section: Density Of Galaxiesmentioning
confidence: 90%
See 2 more Smart Citations
“…But DM rules also the central galaxy regions (Gerhard et al 2001;Padmanabhan et al 2004;Cappellari et al 2006;Thomas et al 2007;Cardone et al 2009; Thomas et al 2009;Hyde & Bernardi 2009b;Tortora et al 2009;Auger et al 2010;Cardone & Tortora 2010;Thomas et al 2011;Cardone et al 2011;Tortora et al 2012;Tortora et al 2014b;Shu et al 2015;Nigoche-Netro et al 2016), in a way substantially consistent with the concordance ΛCDM scenario Napolitano et al 2010;Tortora et al 2012). Different works have shown that the central DM fraction (typically within one effective radius, Re hereafter) is higher in larger and more massive galaxies (e.g.…”
Section: Introductionmentioning
confidence: 65%